Renewal Of Building Use Rights That Expire At The Malang Regency Land Office - Faya M., Bonick (Universitas Islam Malang, 2025)
ABSTRACT: Land registration aims to ensure legal certainty and certainty of land rights. With the implementation of land registration, the parties concerned can easily find out the status of the legal position of the particular land they face, its location, area and boundaries. The right to use buildings in the western legal sense before conversion comes from opstal rights stipulated in Article 71 of the Civil Code that